Environmental design consideration for courtyards in residential buildings in hot-humid climates: A review - Zakaria, Mohd Azuan; Kubota, Tetsu (Penerbit UTM Press, 2014)
This paper discusses environmental design considerations for courtyards in residential buildings in hot-humid climates through a literature review by contrasting with those in hotdry climates. The main focus of discussion is on shading and ventilation effects of courtyards. The results of the analysis revealed that the form and orientation of a courtyard were less significant in its environmental design considerations for the hot-humid climates. Although these factors were reported to be the most important design considerations in the case of hot-dry climates. Mean-while, natural ventilation has been commonly utilized in woodenstructured traditional build-ings in hot-humid climates. However, most of the urban houses in Southeast Asian regions are becoming heavy-weight brick-walled buildings nowadays. It could be seen that the required environmental effects of a courtyard and its design considerations in the case of high thermal mass buildings in hot-humid climates are still uncertain and need to be investigated further.